The Design of a Social Campaign of Third Culture Kids Using Instagram - Nadhiva, Dalila; Apsari, Diani; Haswati, Sri Maharani Budi (Universitas Telkom, 2022)
Many of these families begin having children outside of their home country, and the children that grew up there are known as Third Culture Kids (TCK). They define the